Seismic Performance of Cladding-Panel-Equipped Frames with Novel Friction-Energy-Dissipating Joints - Xi-Long Chen; Xian Gao; Li Xu; Jian-Wen Zhao; Lian-Qiong Zheng (Buildings)
Based on the need to enhance the seismic performance of point-supported steel frame precast cladding panel systems, this study proposes a novel friction-energy-dissipating connection joint. Through establishing refined finite element models, low-cycle reversed loading analyses and elastoplastic time-history analyses were conducted on three frame systems. These included a benchmark bare frame and two cladding-panel-equipped frame structures configured with energy-dissipating joints using different specifications of high-strength bolts (M14 and M20, respectively). The low-cycle reversed loading results demonstrate that the friction energy dissipation of the novel joints significantly improved the seismic performance of the frame structures. Compared to the bare frame, the frames equipped with cladding panels using M14 bolts demonstrated 10.9% higher peak lateral load capacity, 17.6% greater lateral stiffness, and 45.6% increased cumulative energy dissipation, while those with M20 bolts showed more substantial improvements of 22.8% in peak load capacity, 32.0% in lateral stiffness, and 64.2% in cumulative energy dissipation. The elastoplastic time-history analysis results indicate that under seismic excitation, the maximum inter-story drift ratios of the panel-equipped frames with M14 and M20 bolts were reduced by 42.7% and 53%, respectively, compared to the bare frame. Simultaneously, the equivalent plastic strain in the primary structural members significantly decreased. Finally, based on the mechanical equilibrium conditions, a calculation formula was derived to quantify the contribution of joint friction to the horizontal load-carrying capacity of the frame.